Activity and stability of a CuO/CeO2 catalyst for methanol steam reforming - Tonelli, Franco (2015)
The activity and stability of copper supported on cerium oxide have been investigated in the selective production of hydrogen via methanol steam reforming. The catalytic runs were carried out under two different operating regimes: continuous and discontinuous. The main products were H2 and CO2 and a minor amount of CO (selectivity to CO was around 6% at 300 °C). In all the cases, the catalyst was initially very active and the activity was lost with the time on stream. The catalyst under a continuous regime was easily regenerated by air at 400 °C. Under a discontinuous mode, the catalyst was self-activated after stop operation and initial conversion was almost recovered. The deactivation could be mainly attributed to the adsorption of carbonate species which were easily desorbed under an inert flow or by burning with air. The pre-reduction of catalyst should be avoided to reach higher stability.